PETAKOM payment tracking system - Sarah Nabiha, Hamdan (2018)
This project is built to facilitate the organization of the PETAKOM to track payments made by students more organizationally, easily, fast, cost-saving and environmentally friendly. Of the detectable problems such as paper usage every time a payment is made it will take time to retrace the required data and possibly also for lost data. RAD is used as a methodology for Petakom Payment Tracking System project development. This Petakom Payment Tracking System concept is to track Petakom student payments more easily, organizationally and quickly.